Effectiveness and Safety of Whole-Body Electromyostimulation on Musculoskeletal Diseases in Middle Aged-Older Adults – A Systematic Review - Le, Y. H.; Kohl, M.; von Stengel, Simon; Uder, Michael; Kemmler, Wolfgang (Deutsche Zeitschrift für Sportmedizin, 2024)
› Whole-Body electromyostimulation (WB-EMS) is a time-effective, joint-friendly and consistently supervised exercise training technology particularly attractive to address health-related outcomes in middle-age to older adults. The present systematic review aims to summarize WB-EMS effects on musculoskeletal diseases and conditions in corresponding non-athletic cohorts. › A systematic search in five electronic databases, two study registers and a hand search in Google Scholar without language restrictions up to March 2023 was conducted. We included only peer reviewed clinical trials and intervention studies on WB-EMS with non-athletic adult cohorts averaging 45 years and older addressing musculoskeletal diseases and conditions. Case reports, review articles, editorials, conference abstracts, or theses were not considered. › Nineteen research projects with 22 articles focusing on the effect of WB-EMS on musculoskeletal diseases and conditions were identified. In summary high evidence for positive effects were reported for non-specific chronic low back pain and sarcopenia. Moderate evidence was provided for positive effects on knee osteoarthritis and non-significant positive effects on osteopenia. While two out of eight studies reported minor increases of biomarkers related to rhabdomyolysis, one study reported a single case of mild rhabdomyolysis after a WB-EMS session. No study reported clinically relevant adverse effects. › In summary, we have provided further evidence for predominately positive effects of WB-EMS on musculoskeletal diseases and conditions along with a lack of clinically relevant adverse effects related to WB-EMS application in middle-aged and older cohorts.
CRIS-Team Scopus Importer:2024-05-31
Keywords: Cohorts; Complaints; Neuromuscular Electromyostimulation; Training; WB-EMS